2021
DOI: 10.3389/fmicb.2021.655390
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Syngas Fermentation With Clostridium carboxidivorans in Stirred-Tank Reactors With Defined Gas Impurities

Abstract: Syngas fermentation processes with acetogenic bacteria like Clostridium carboxidivorans have been proven to be a promising approach for the conversion of CO-rich waste gases into short- and medium-chain alcohols. The challenge of synthesis gas impurities, on the other hand, has always been a major concern for establishing an industrial-scale process, since some of the trace components in waste gases, such as NH3, H2S, and NOx, can have inhibiting or even toxic effects on microbial growth and product formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
1
38
1
Order By: Relevance
“…Using a continuous gas-fed bioreactor, Fernández-Naveira et al (2016) obtained 5.55 g/L of ethanol and 2.66 g/L of butanol; however, hexanol was not produced. Rückel et al (2021) reported the production of hexanol using a fermenter but the concentration was only 0.16 g/L. Shen et al (2017) optimized the composition of trace metals in the medium to enhance alcohol production and applied a timed control incubation temperature (37°C for 0–24 h, 25°C for 24–144 h), yielding a total alcohol titer of 6.97 with 1.67 g/L butanol and 1.33 g/L hexanol.…”
Section: Resultsmentioning
confidence: 99%
“…Using a continuous gas-fed bioreactor, Fernández-Naveira et al (2016) obtained 5.55 g/L of ethanol and 2.66 g/L of butanol; however, hexanol was not produced. Rückel et al (2021) reported the production of hexanol using a fermenter but the concentration was only 0.16 g/L. Shen et al (2017) optimized the composition of trace metals in the medium to enhance alcohol production and applied a timed control incubation temperature (37°C for 0–24 h, 25°C for 24–144 h), yielding a total alcohol titer of 6.97 with 1.67 g/L butanol and 1.33 g/L hexanol.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the by-product trimethylamine is triggered when ammonia is present in syngas. For syngas fermentation, one study concludes that ammonia reduces cell growth and inhibits hydrogenase [169], while increased cell growth and ethanol formation are observed in another study [170].…”
Section: Tolerance Of the Catalyst To Syngas Impuritiesmentioning
confidence: 98%
“…Substrate inhibition can occur if too much gas is transferred into the liquid phase [137,162,[164][165][166][167][168]. Syngas impurities also influence the fermentation process [163,[169][170][171] (see Sect. 4.1).…”
Section: Operating Conditionsmentioning
confidence: 99%
“…The schematic of the production of various small-chain and long-chain chemicals from the CO2 conversion using MES and carbon biocathodes is shown in Figure 5. 111 , where a gas-liquid mass transfer can be boosted through increasing impeller speed, which separates the gas stream into smaller bubbles with a higher specific surface area 112 . Acetate is among the most widely prepared small chain value-added products from CO2 conversion in MES.…”
Section: Product Selectivitymentioning
confidence: 99%